(untitled) (LACCEI, 2024)
In Peru, the textile and clothing sector is considered the third activity with the highest market share and with the greatest contribution to the national economy. Much of this industry is made up of small and medium-sized businesses, which generate the largest number of jobs. However, most of these companies present problems in factors such as quality, high production times and low availability of machinery, which hinder better performance in the market and undoubtedly affect competitiveness. The present research work aims to increase production efficiency in a garment line based on Lean Manufacturing tools. Which proposes a model based on the use of tools such as 6S, SLP, TPM (2 pillars), Study of methods, time, and motion study. The results of the application of the proposed model with each of the tools were taken periodically until an improvement of 13% was obtained in the indicator of Overall equipment efficiency (OEE).